DEVELOPMENT OF ADMINISTRATIVE SKILLS: HOW TO IMPROVE BUSINESS ANALYSIS, PROBLEM SOLVING, AND CRITICAL THINKING (International Seven Journal of Multidisciplinary, 2022)
Effective administrative skills are essential for navigating the complexities of modern organizational environments. This article explores the development of three key competencies: business analysis, problem-solving, and critical thinking. It discusses how these interrelated skills contribute to strategic decision-making, operational efficiency, and organizational adaptability. Drawing on academic literature, the article highlights practical approaches to skill enhancement, such as experiential learning, data-driven training, and reflective practices. The integration of these competencies empowers professionals to make informed decisions, anticipate challenges, and drive continuous improvement within their organizations.